Novel NDE techniques in the power generation industry - Ward, Christopher M. S. (2010)
The thesis presented here comprises the work undertaken for research into novel NDE techniques in the power generation industry. This has been undertaken as part of the Engineering Doctorate Scheme run by the Research Centre for Non-Destructive Evaluation (RCNDE), which aims to bridge the technological gap between university research and industrial application. In this case, the scheme consisted of two projects completed in conjunction with RWE npower looking at current NDE problems in steam turbine and steam-raising plant. The first project was concerned with detecting microstructural transformation in steam turbine blades, which can act as a precursor to failure by environmentally assisted cracking. This project, and indeed, this entire thesis is principally based on electromagnetic testing methods. An eddy current technique for mapping the microstructural phases was produced and validated as far as was achievable; this offered a significant time-saving advantage over the previous method, by reducing inspection time from 5 man days to just 1.5. The technique has novelty in producing a 2-dimensional map of the blade surface which highlights areas where microstructural phases differ. The second project focuses on the detection of microstructural damage associated with material creep life expiry. This forms a review of the current state of technology and highlights potentially useful paths for future research in both established and emerging NDE technologies, including Magnetic Barkhausen Noise testing and laser-generated ultrasound. Both projects have provided tangible benefit to the sponsoring company and have pushed forward research in a number of technological applications.